The Effect of Raw Material Cost and Direct Labor Cost on Selling Prices in Manufacturing Companies in the Consumer Goods Industry Sector of the Pharmaceutical Sub-Sector Listed on the Indonesia Stock Exchange - Firmansyah, Indra; Damanik, Bobby Pranata (GoAcademica Research & Publishing, 2024)
Covid 19 is a phenomenon that occurs in the world, especially Indonesia, in dealing with this phenomenon, of course the health sector is at the forefront of dealing with Covid 19, especially in the pharmaceutical sector which provides various types of drugs. With the large demand and scarcity of medicines and supplements to maintain immunity to avoid the spread of Covid 19, the raw materials for medicines have experienced a significant increase in prices. The Effect of Raw Material Costs and Direct Labor Costs on Selling Prices in Manufacturing Companies in the Consumer Goods Industrial Sector in the Pharmaceutical Sub-Sector Listed on the Indonesia Stock Exchange (IDX) is a research project the authors are interested in undertaking based on the phenomena that they observe. both individually or simultaneously. The research carried out is quantitative research with the hypothesis used, namely the two-party test. The analytical technique used is the Normality Test, Product Moment Correlation Test, Multiple Correlation Test, Multiple Linear Regression Test, Coefficient of Determination, T Test, F Test. Statistical calculations using SPSS Version 26.